PENGARUH FAKTOR UDARA TERHADAP PARAMETER OPERASI FLUIDIZED BED GASIFIER BIOMASSA - Rahardjo, Bambang Suwondo (Jurnal Energi dan Lingkungan (Enerlink), 2009)
Development on fluidized bed gasification of biomass has been initiated byYayasan Dian Desa collaboration with NEDO (New Energy and IndustrialTechnology Development Organization of Japan) starting from small scale(2000–2003), bench–scale tests (2004–2005) and pilot–plant (2006–2009). Since2006, a cooperative research and development on fluidized–bed gasification ofbiomass established and agreed between the BPP Teknologi, Yayasan DianDesa and NEDO to investigate the influence of the air factor on other gasifieroperation parameters: bed temperature, gas calorific value and gasifier coldefficiency. The experiments were carried out with the following kinds of biomass:rice husk, sawdust, sugarcane bagasse and spent coffee grounds. Therelationship between the gasifier cold efficiency and air factor shows that thecurves for rice husk and sawdust have a maximum; for bagasse the relationshipis decreasing because of intensive elutriation; for spent coffee grounds due tofeeder limitations, it was not possible to feed the biomass flow corresponding toair factor values greater than 0.2. The low efficiency values are a consequence ofthe lack of thermal insulation in the freeboard zone.Kata kunci: fluidized bed, gasification, biomassa